(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2020)
The task of educational institutions should not just be information and skills training but to inculcate values among the learners for their development. Values education serves as a springboard for every learner’s development in different aspects. This study’s main purpose was to determine the level of development of the senior high school students of Union Christian College during the School Year 2019-2020. The predictive effect of the school aspects -people, process, and place -on the development of the respondents was also explored. The descriptive correlation method of research analysis was employed. 100 Grade 12 Senior High School students and their parents, and the SHS teachers at Union Christian College consented to participate in the study. The survey questionnaire adopted from Gracia (2019) was the main data gathering tool used. The researchers used weighted mean, regression analysis, and ANOVA for the treatment of data. The study revealed that the learner’s level of development along character traits, positive discipline, and academic as rated by the three groups of respondents were moderately developed. Furthermore, these areas of development were highly influenced by the school constituents, namely people, process, and place. Meanwhile, the learners and their parents showed agreement in their assessment of the learners’ level of development and the extent of influence of the factors on these developments. Lastly, the three school constituents -people, process, and place -were found to be predictors of the student development in the identified areas, having people as ranked 1 of these predictors followed by processes, then place. The above findings further confirm the impact of school on learners’ development, particularly on how the school aspects interplay in their lives. Given these conditions, the weak areas shall be revisited for improvement. Then replications of this study can be conducted to establish the trend on how students perceived the influence of school in their lives.